Development of Depik Fish (Rasbora tawarensis) Based Functional Snacks A Local Food Innovation for Community Empowerment - Griantara, Wira Nahma; ramadhani, evi; Alfiani, Emi Tri; Zaraska, Marsha Febry; Maulana, Zaky Alif; Manurung, Bintang Najwa (Universitas Syiah Kuala, 2025)
The rise of healthy lifestyles alongside low fish consumption among young people presents a challenge to local food security. Depik fish (Rasbora tawarensis), an endemic species of Lake Laut Tawar, is rich in protein and omega-3 fatty acids, which offer significant health benefits; yet, its utilization remains limited. This study aims to develop Elpis, a snack derived from Depik fish, while evaluating public perceptions, preferences, and acceptance of the product. A descriptive quantitative online survey was conducted with 50 adolescent and young adult respondents, using a questionnaire that provided information on the product and its nutritional content. The findings indicate that 84% of respondents are willing to try the product if its taste and appearance are appealing, while 75% recognize the nutritional benefits of Depik fish. Elpis has the potential to enhance fish consumption, create local business opportunities, and empower fishermen through supply chain partnerships. By combining innovation based on local ingredients with principles of sustainable entrepreneurship, this approach generates economic, social, and environmental value simultaneously. In conclusion, Elpis serves as a model for adaptive, sustainable, and educational local food innovation for the younger generation, while contributing to the achievement of sustainable development goals.